Semen quality, testicular B-mode and Doppler ultrasound, and serum testosterone concentrations in dogs with established infertility - de Souza, Mírley B.; England, Gary C.W.; Mota Filho, Antônio Cavalcante; Ackermann, Camila Louise; Sousa, Carmen Vládia S.; de Carvalho, Gabriela G.; Silva, Herlon Victor Redrigues; Pinto, José N.; Linhares, Jussiara C.S.; Oba, Eunice; da Silva, Lucia Daniel Machado (Elsevier, 2015)
Retrospective examination of breeding records enabled the identification of 10 dogs of normal fertility and 10 dogs with established infertility of at least 12 months of duration. Comparisons of testicular palpation, semen evaluation, testicular ultrasound examination, Doppler ultrasound measurement of testicular artery blood flow, and measurement of serum testosterone concentration were made between the two groups over weekly examinations performed on three occasions. There were no differences in testicular volume (cm3) between the two groups (fertile right testis = 10.77 ± 1.66; fertile left testis = 12.17 ± 2.22); (infertile right testis = 10.25 ± 3.33; infertile left testis = 11.37 ± 3.30), although the infertile dogs all had subjectively softer testes compared with the fertile dogs. Infertile dogs were either azoospermic or when they ejaculated, they had lower sperm concentration, sperm motility, and percentage of morphologically normal spermatozoa than fertile dogs. Furthermore, infertile dogs had reduced sperm membrane integrity measured via the hypoosmotic swelling test. Infertile dogs had significantly lower basal serum testosterone concentrations (1.40 ± 0.62 ng/mL) than fertile dogs (1.81 ± 0.87 ng/mL; P < 0.05). There were subjective differences in testicular echogenicity in some of the infertile dogs, and important differences in testicular artery blood flow with lower peak systolic and end-diastolic velocities measured in the distal supratesticular artery, marginal testicular artery, and intratesticular artery of infertile dogs (P < 0.05). Notably, resistance index and pulsatility index did not differ between infertile and fertile dogs. These findings report important differences between infertile and fertile dogs which may be detected within an expanded breeding soundness examination.